CYTOGENETIC STUDY OF THE HAMDANI SHEEP BREED OF THE IRAQI KURDISTAN REGION - D. M. Khdhr; K. J. Karim (مجلة الأنبار للعلوم الزراعية)
This study presents a cytogenetic analysis of the local Hamdani sheep breed found in the Iraqi Kurdistan region, as it has an economic and agricultural industrial role. The main objective of this research was to understand the cytogenetic characterization involving the karyotyping of chromosomes (numbers and structure) of ten rams and fifteen ewes Hamdani sheep). The results indicated that the chromosomal numbers of 54(2n) and 52 chromosomes are autosomes with two sex chromosomes (XY in males and XX in females). The first three pairs of autosomes were submetacentric in both sexes. The relative lengths in the first three pairs in male sheep were 7 17,7,13 and 7.13µmcompared to 7,10,7.08 and 7.05µm for the females. The sheep's 4th to 26th pairs of chromosomes were acrocentric, and their relative lengths decreased progressively from the 4th to the 26th. For male sheep, the X chromosome was acrocentric with a relative length of4.48µm, whereas the Y chromosome was submetacentric at 3.30µm. Both X chromosomes in female sheep were acrocentric and had the same relative length of 3.46µm. The first three pairs of male chromosomes had the same arm's length ratio (ARM ratio) of1.00µm, and their centromere index was the same at 49.87µm. All first three pairs of female chromosomes had the same ARM ratio at 1.00µm, and their centromere indexes were 49.98, 49.89, and 49.91µm, respectively. The karyological analysis of this sheep indicated normal chromosomal complements without any abnormalities. This normal chromosome profile indicates sheep with promising reproductive health and fertility status.